The role of accounting knowledge in supporting and enhancing accounting practice in light of the internationalization of accounting education - RASHWAN, Abd El Rahman Mohmmed; Abu Arab, Heba H.M. (Journal of Finance & Corporate Governance, 2021)
The study aimed to identify the role of accounting knowledge in supporting and enhancing accounting practice in light of the internationalization of accounting education, in order to answer the questions and test the hypotheses of the study, the researchers relied on the descriptive-analytical approach, and to obtain the relevant data, a questionnaire was distributed after its evaluation to the study population. The results of the study proved that there is a role for scientific, technical and practical accounting qualification in promoting accounting practice in light of the internationalization of accounting education. The study recommended the necessity of taking into account the development plans in universities to provide time for faculty members in the accounting departments in Palestinian universities to develop their scientific knowledge in line with the internationalization of accounting education.